What's love got to do with it? Relationship quality appraisals and quality of life in couples facing cardiovascular disease - Bouchard, Karen; Gareau, Alexandre; Greenman, Paul S.; Lalande, Kathleen; Sztajerowska, Karolina; Tulloch, Heather (Health psychology & behavioral medicine, 2023)
Changes in couples' relationship quality are common post-cardiac event but it is unclear how relationship quality is linked to patients' and spouses' quality of life (QoL). The purpose of the present study was to examine the association between relationship quality on QoL in patient-spouse dyads within six months of a cardiac event. Participants (N = 181 dyads; 25.9% female patients), recruited from a large cardiac hospital, completed validated questionnaires measuring demographic, relationship (Dyadic Adjustment Scale; DAS) and QoL variables (Heart-QoL & Quality of life of Cardiac Spouses Questionnaire). An Actor-Partner Interdependence Model was used to investigate actor (i.e. responses influencing their own outcome) and partner effects (responses influencing their partner's outcome) of relationship quality and QoL. Patients' and spouses' perceptions of relationship quality were in the satisfied range (DAS > 108; 65% of sample) and, as expected, patients reported lower general physical QoL than did their spouse (t (180) = −10.635, p < .001). Patient and spouse relationship quality appraisals were positively associated with their own physical (patient β = .25; spouse β = .05) and emotional/social (patient β = .21; spouse β = .04) QoL. No partner effects were identified. High quality relationship appraisals appear to matter for patients' and spouses' QoL after the onset of CVD.